Drug Utilization Evaluation of Proton Pump Inhibitors in the General Medicine Ward of a Tertiary Care Hospital - Hiremath, Shivalingayya Gadagayya; Chaudhary, Umesh; Sreekanth, Giridhar Koratagere; Ravishankar, Sai Keerthana; Devaraj, Manikanta; Yadav, Shailesh (International Journal of Pharmaceutical Investigation, 2026)
Background Proton Pump Inhibitors (PPIs) are the most effective agents for managing acid related disorders. However, Inappropriate Prescribing of PPIs is becoming an issue of concern. Purpose To review proton pump inhibitors prescribing pattern, common drugs prescribed along with PPIs and Drug Interaction. Materials and Methods A prospective observational study was carried out over a period of three months in a tertiary care hospital, adhering to predefined inclusion and exclusion criteria. Results A Total number of 205 patients, PPIs prescriptions 190 (93%), Non-PPIs prescriptions 15 (7%), from the PPIs prescription, 95 (50%) male and females 95 (50%). Among all age groups, 59-68 years 35 (18.42%) age groups had the highest number of prescribed with PPIs and age group of 89-98 years 4 (2.10%) had the lowest prescribed with PPIs. Maximum concomitantly prescribed with PPIs are antibiotics165 (14.01%) and least prescribed drugs are anti-tb drugs, 1 (0.08%) and anti-spasmodic,1 (0.08%). PPIs utilization more was pantoprazole 177 (93.15%) and less was esomeprazole 13 (6.84%) more duration prescribed PPIs was more than four days 96 (51%), less prescribed duration was one to two days 33 (17%), more used route of administration was parenteral 133 (70%), less used route of administration was oral and parenteral 25 (13%), about drug interaction major 1 (3%), moderate 20 (59%) and minor 13 (38%). by NICE guidelines, the majority of prescriptions are appropriate 137 (72%) and in-appropriate prescription was found 53 (28%). Conclusion The widespread use of Proton Pump Inhibitors (PPIs), particularly pantoprazole, often deviates from established guidelines, with many physicians prescribing them for gastro-protection alongside NSAIDs or antimicrobials. This practice increases the risk of drug-drug interactions, underscoring the need for prescriber awareness and adherence to guidelines. Educational programs and clinical pharmacist involvement can promote rational PPI use, improving patient outcomes and reducing healthcare costs.
Keywords: Proton Pump Inhibitors; Prospective; Non-steroidal anti-inflammatory drugs; National Institute of Clinical Excellence.